Autochthonous microalgae grown in municipal wastewaters as a tool for effectively removing nitrogen and phosphorous. (December 2020) - Lima, Serena; Villanova, Valeria; Grisafi, Franco; Caputo, Giuseppe; Brucato, Alberto; Scargiali, Francesca
Graphical abstract: Highlights: Isolated microalgae from Sicily were tested for urban sewage treatment. Indigenous microalgae grew in sewage better than collection strains. A consortium of Dunaliella sp. and Chlorella gave rise to the best growth performance in sewage. Microalgae were found to be effective in removing TN (up to 77 %) and TP (up to 61 %) from urban sewage. Abstract: Microalgae have promising applications in wastewater treatment because of their ability to use inorganic compounds such as nitrates and phosphates as nutrients for their growth. Microalgae are applied to the secondary and tertiary bio-treatment with two benefits: i) pollutants removal from wastewater; ii) production of microalgal biomass, that can be exploited as a source of biomass and biomolecules. In the present work, four different microalgal strains (two from culture collections and two isolated from Sicilian littoral) were tested in municipal sewage bioremediation. The sewage of a municipal plant, already processed with primary treatment, was used for the cultivation of microalgal strains in order to test their potential on performing the secondary treatment. Microalgal cells were cultivated in growth medium and in sewage with the aim to compare their growth and biomass composition in different conditions. The efficiency of wastewater treatment was established through assessment of biochemical oxygen demand (BOD), chemical oxygen demand (COD), total nitrogen (TN) and total phosphorous (TP) of sewage before and after algal growth. Results showed that microalgal treatment alone is not effective in reducing COD and BOD, while all the tested strains were able to significantly reduce wastewater TN (up to 77 %) and TP (up to 61 %) concentrations. Amongst the tested strains, Chlorella genus can be considered the best candidate for wastewater treatment.